A New Flavonoid from the Roots of Cassia fistula and Its Antitobacco Mosaic Virus Activity - Zeng, Xiaoying; Zhao, Wei; Zhang, Tao; Wang, Lan; Yang, Guangyu; Chen, Yong-Kuan; Hu, Qiufen; Miao, Mingming (Asian Journal of Chemistry, 2013)
A new flavonoid, fistulaflavonoid A (1), was isolated from the roots of Cassia fistula. Its structure was elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Compound 1 was tested for their antitobacco mosaic virus activity. The compound shows modest antitobacco mosaic virus activity with inhibition rates of 18.2 %.